Collaborative Dynamics dalam Penanganan Stunting Melalui Program Ma’silambi di Desa Duampanua Kabupaten Polewali Mandar - Rizal Pauzi; Nurmadina Jamhur; Saddam Husain Tamrin; Muh Tang Abdullah (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Stunting is a serious public health issue in Indonesia, including in Duampanua Village, Polewali Mandar Regency, which has a high prevalence of stunting. Addressing stunting requires collaboration among various parties, including the government, community, and relevant sectors. This study aims to analyze the collaborative dynamics in addressing stunting through the Ma’silambi Program in Duampanua Village, based on the Collaborative Dynamics theory proposed by Emerson et al. (2012), which includes principled engagement, shared motivation, and capacity for joint action. The approach used in this study is qualitative with a case study research design. Data were collected through interviews with 10 informants consisting of government stakeholders, community members, and other related parties, as well as program documentation analysis. The findings of the study show that although community participation is high, collaboration among stakeholders is still not effective. Several factors hindering the effectiveness of collaboration include unclear role distribution, lack of binding regulations, absence of routine meetings, and inadequate support for all involved parties. As a result, achieving zero stunting in Duampanua Village remains difficult. This study recommends that the village government and the health department clarify the roles of each stakeholder, improve communication and coordination, and establish a binding Village Regulation (PERDES) related to the Ma’silambi program. Future research is expected to examine external factors affecting the success of collaboration, such as socioeconomic factors and government policies.